CHARACTERISTICS AND CONTENT OF THE IDEAL TYPES OF POLITICAL REGIMES - Madina Maksharipovna Khamatkhanova; Israpil Magometovich Sampiev (Современная наука и инновации, 2022)
The article identifies the characteristics of various types of political regimes, considered as ideal types. Following the most common classifications of political regimes, consistently analyzes the content and parameters sultanian, totalitarian, authoritarian and democratic regimes